MELCOR simulation of core thermal response during a station blackout initiated severe accident in China pressurized reactor (CPR1000). (May 2015) - Wang, Jun; Zhang, Yapei; Mao, Keyou; Huang, Yujia; Tian, Wenxi; Su, Guanghui; Qiu, Suizheng
Abstract: Interest in evaluation of reactor response and off-site consequences following beyond design basis accidents has significantly increased after Fukushima. MELCOR is an advanced computational aid that has been widely used and adapted to various reactor designs for severe core damage analyses. This paper summarizes the core thermal hydraulic response for a hypothetical severe accident caused by station blackout with failure of the steam generator safety relief valve at a Chinese pressurized reactor 1000-MW power plant – CPR1000 using MELCOR. Analytical results for a) temperature distribution of the fuel pellets, b) the fuel cladding, c) flow rate of the coolant, and, d) hydrogen mass changing over time are presented. The analyses are focused on safety assessment of the reactor core for severe accidents and are part of the overall evaluation of safety features of the CPR1000 reactor for residual risk posed by severe accidents. Highlights: MELCOR simulation of core thermal response during a severe accident CPR1000 was conducted. An original investigation in severe core damage accident is presented. Consequences assessments lead to qualification of the mitigation strategies.